2021
DOI: 10.1002/ehf2.13187
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of H2FPEF score in patients with heart failure with preserved ejection fraction

Abstract: Aims The H 2 FPEF score is a convenient risk stratification tool for diagnosing heart failure with preserved ejection fraction (HFpEF). This study examined the value of the H 2 FPEF score for predicting all-cause mortality and rehospitalization in HFpEF patients. Methods and results This was a retrospective cohort study of patients diagnosed with HFpEF by echocardiography at a single tertiary centre between 1 January 2015 and 30 April 2018. According to the H 2 FPEF score, the subjects were divided into low (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 25 publications
1
37
1
1
Order By: Relevance
“…Surprisingly, these common comorbidities showed no positive correlation with all-cause death after being fully adjusted, except for diabetes. AF and HFpEF commonly coexist and share common epidemiology, pathophysiology, pathogenesis, and risk factors (34). Both the prevalence and incidence of AF are associated with the increased mortality in HFpEF (35).…”
Section: Comorbidities and Prognostic Factors In Hfpefmentioning
confidence: 99%
“…Surprisingly, these common comorbidities showed no positive correlation with all-cause death after being fully adjusted, except for diabetes. AF and HFpEF commonly coexist and share common epidemiology, pathophysiology, pathogenesis, and risk factors (34). Both the prevalence and incidence of AF are associated with the increased mortality in HFpEF (35).…”
Section: Comorbidities and Prognostic Factors In Hfpefmentioning
confidence: 99%
“…The latest data show that the prevalence of HFmrEF in hospitalized patients ranged from 13 to 26% (9)(10)(11), while the prevalence in outpatients varied from 9 to 21% (12)(13)(14)(15)(16)(17). Nevertheless, previous studies mostly focused on HFrEF and HFpEF, with less attention paid to HFmrEF until now (18,19). Consequently, less is known regarding the clinical characteristics of patients with HFmrEF, and with limited evidence on which to base recommendation for therapy (20).…”
Section: Introductionmentioning
confidence: 99%
“…The widely used H2FPEF and HFA-PEFF scores were designed as diagnostic tools and were validated only on hospitalized, acute HFpEF population. The H2FPEF score might be a potentially useful marker for the prediction of cardiovascular and HF-related events in HFpEF patients ( 5 , 52 ). Sotomi et al found that the HFA-PEFF score is an excellent diagnostic tool, and it also has a practical prognostic value ( 4 ).…”
Section: Discussionmentioning
confidence: 99%